THAI BUSINESS GROUP IN LAOS DAM PROJECT IN MEKONG RIVER - Patimah Basor (HI 16 UMY 121, 2016)
Mekong River is known as an international river of Asia passing through six countries, first starting from China, Myanmar, Laos, Thailand, Cambodia and Vietnam. There are around 60 million resident depending on Mekong River area. Mekong River is daily life of many resident in Mekong river area and countries lower Mekong River. By building a dam, there will be a lot of impact such as flood, fishery, transportation and agriculture. Those impacts will influence countries lower Mekong directly. Due to this problem Cambodia, Vietnam and Laos dispute over the impact. However, Thai government decided to support the dam project. Some developers of the dam project Laos in Mekong River are Thai companies. In the dam project, Thai company got benefit because of developer, However, Thailand got impact direct because Thailand is country under Laos, but Thai government agree to buy electricity from Lao’s dam project. In fact, Thai electricity is sufficient to fulfil the energy need of the country. The decision making of Thai government has Thai business influence; that undergraduate thesis will be explain why Thai government support the project dam of Lao in Mekong River. Keywords: Mekong River, Thailand government, Thai business, dam project.